The Impact of Reading Interest and Learning Habits on Students' Achievement for Integrated Science Learning - Fitri (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
The objective of this study is to determine 1) how reading interest affects students' integrated science learning achievement. 2) The impact of students' learning behaviors on their science learning achievement 3) Effects of students' reading preferences and study practices on their integrated science learning achievement. This study is an example of correlational ex post facto research. The population of this study consisted of all students, totaling 470, from whom a sample of 150 was drawn using stratified random sampling methods. Questionnaires and documentation are used in the data retrieval approach. Regression analysis is the method of data analysis used. Results indicate that 1) reading interest has a significant impact on students' integrated science learning achievement, with a value of 0.000 (0.05), and that reading interest contributes relatively to 36.5% of students' integrated science learning achievement. 2) There is a substantial relationship between learning habits and students' integrated science learning achievement, with a significance level of 0.000 (p 0.05) and a relative contribution of 16.2% from learning habits. 3) With a value of 0.000 significance (0.05), there is a significant relationship between reading interest and learning habits and the achievement of integrated science learning students. Together, these two factors account for 36.5% of the students' integrated science learning achievement.